The Negros Millenarian Movements - Cleope, Earl Jude Paul L. (Silliman Journal, 2022)
This paper presents the millenarian movements of Negros Island specifically in the southernpart where topographic conditions significantly influenced the emergence and subsequent reappearance of what is sometimes labeled as "revitalization movements." Further this paper aims to present the various peasant movements with their religious undertones which appeared in Negros as influ-enced by babaylanism from nearby Panay Island. Negros Island saw the prolif-eration of religio-political protest movements that attracted many rural adher-ents. Classified as messianic, nativistic, or millenarian, these movements com-bine folk, Catholic, political, and nationalistic ingredients in their ritual be-liefs and practices. Using a New Historicist approach and ethnography, this paper tries argues that poverty, social inequities, social disorder, and anxieties have pro-vided the backdrop for the emergence of these movements. Thus, such movements must be understood in the context of the social, economic, and political condi-tions that gave rise to them. Following this view, this paper attempts to eluci-date the connection between the movement spearheaded by Dios Buhawi in 1888; Papa Isio in the 1890s; the Salvatori in the 1980s; and the contempo-rary Dios Amahan movements which has found fertile breeding ground in the same areas.